2021
DOI: 10.1007/s00167-021-06652-2
|View full text |Cite
|
Sign up to set email alerts
|

Critical shoulder angle does not influence retear rate after arthroscopic rotator cuff repair

Abstract: PurposeThe critical shoulder angle (CSA) has been implicated as a potential risk factor for failure following arthroscopic rotator cuff repair (RCR). However, there is conflicting evidence regarding the clinical usefulness of this measurement. Given these discrepancies and limited comparisons to clinical outcomes, the aim of the current study was to determine whether higher CSAs correlated with an increased retear rate after arthroscopic rotator cuff repair and to determine if any association between CSA and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…25,26 However, some studies have reported opposite results. 4,27 In the present study, CSA values were significantly different between the groups with and without retear, with the maximum value in the FR group. This supports the concept that a wide lateral acromion is associated with postoperative tendon healing, as evidenced by the association of the CSA with failure of postoperative repair.…”
Section: Discussioncontrasting
confidence: 40%
“…25,26 However, some studies have reported opposite results. 4,27 In the present study, CSA values were significantly different between the groups with and without retear, with the maximum value in the FR group. This supports the concept that a wide lateral acromion is associated with postoperative tendon healing, as evidenced by the association of the CSA with failure of postoperative repair.…”
Section: Discussioncontrasting
confidence: 40%
“…In addition, higher CSAs increase the rate of retears following RCR 33–38 . However, other studies have questioned the diagnostic value and reliability of the CSA 39–42 . One important reason fueling the debate was the inherent measurement error of the CSA reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,6,9,10,16,20,22,23 Multiple parameters from plain radiographs, such as critical shoulder angle, acromion index, and lateral acromial angle, showed no relationships with retears. 11,13,43 Studies of the usefulness of MRI-related factors, such as tear size, fatty infiltration, and muscle atrophy as prognostic indicators, have demonstrated relatively few discrepancies. 4,16,18,20,21,24,34 Compared with patient and plain radiograph factors, MRI-related factors are direct and more accurate indicators of tendon status.…”
Section: Discussionmentioning
confidence: 99%
“…3,12,16,23,31,37 Moreover, studies of the associations of findings on plain radiography and magnetic resonance imaging (MRI), such as critical shoulder angle and glenoid inclination angle, with the risk of retears have produced inconsistent results. 11,13,32,45 Furthermore, several studies have evaluated rapid and accurate methods to predict retears based on patient characteristics and imaging studies; however, the results have been inconclusive. 16,22 Fatty infiltration of the rotator cuff is one of the few consistent predictors of retears across multiple studies, as it may reflect the quality of rotator cuff tendons.…”
mentioning
confidence: 99%